Analisis Literatur Tentang Evaluasi Pembelajaran Matematika dan Relevansinya Dengan Kurikulum Merdeka - Runisyah, Runisyah (STKI Harapan Bima, 2025)
This article aims to analyze literature related to mathematics learning evaluation and its relevance to the implementation of the Merdeka Curriculum in Indonesia. Learning evaluation serves not only as a tool to measure learning outcomes but also as a critical instrument for enhancing learning quality, particularly in conceptual understanding and the development of critical thinking skills. Through a literature review of recent studies, this article identifies the importance of holistic, diagnostic, and differentiated assessment approaches as emphasized by the Merdeka Curriculum. However, challenges such as limited teacher competence in designing innovative evaluations and the persistent use of traditional assessment methods are also highlighted. This study recommends ongoing professional development and systemic support to bridge the gap between curriculum theory and classroom evaluation practices. With appropriate assessment strategies, the Merdeka Curriculum's goal of fostering student-centered learning can be optimally achieved, particularly in the context of mathematics education.